The Role of the Subject "Mathematics" Content in the Learning Motivation - NailyaVakifovnaTimerbaeva; Ildarovna Fazleeva, Elmira; Barievna Shakirova, Kadriya (International Journal of Psychosocial Rehabilitation, 2019)
The future of any country depends on the quality of education, in particular, mathematics. This paperrepresents an investigation of the possibilities of using motivation, which is one of the main conditions for improving the quality of teaching mathematics.Educational motivation, as a particular type of motivation, is determined by many factors: the educational system, the organization of the learning process, the subjective characteristics of a student and teacher. In our opinion, the factor associated with the very specificity of the subject matter “mathematics” remains insufficiently studied. Experience has shown that practice teachers and beginning teachers underestimate the role of motivation in teaching mathematics.They unconsciously or quite consciously skip the stage of motivation when introducing mathematical concepts, studying theorems, etc., not seeing the potential of the subject matter for the implementation of motivation.The purpose of the study is to identify the capabilities of the subject matter “mathematics” in the implementation of motivation, as well as the pedagogical conditions for preparing future teachers for its implementation. The research methods for this problem are the theoretical analysis of the knowledge of this issue, questionnaires, overt observation. The study showed that students and beginning teachers knowing the general techniques and methods of motivation do not see the potential possibilities of the subject of mathematics and specific topics for its implementation.At the same time, we have established that motivation can be carried out at any stage of training: by introducing mathematical concepts, algorithms, studying methods of action, methods for solving problems and theorems. Improving the training of future mathematics teachers is associated with the development of mathematical, pedagogical and methodological thinking of students, allowing motivation to introduce to study mathematics as a subject.To do this, in the classes on the teaching methodology, it is worth to purposefully teach the methods of motivation for educational activity in all substantive lines of the school course in mathematics to supplement the training content with courses on the choice of “Methods of student motivation”, “The role of motivation in teaching mathematics”, “Motivation for learning through the content of the subject.